Human talent management in MICRO and SMES of Barranquilla - Cabarcas Velásquez, Marcos
Human talent management involves processes of selection, induction, training, performance evaluation,compensation and health and safety at work; a proper management allows organizations to improve theiremployees’ well-being, which ends up being reflected in improvements in productivity and performance ofthe organization. In accordance with the above, this article aims to analyze the processes that make up humantalent management – HTM (GTH) - in micro, small and medium enterprises –MSMEs -, of several sectors in thecity of Barranquilla. Diagnosing these processes is intended through a descriptive quantitative analysis. Theselected sample corresponded to 94 companies of MSMEs of Barranquilla. The results make evident the lackof a human talent management area, and in those companies where it exists, the processes are not appliedcorrectly. The process mostly used is compensation; while the selection is little used and the rest is not applied.